MOMENT OF SILENCE IN MEMORY OF JANUARY 20 SHAHIDS (AzerTAc, 2008)
Hundreds of thousands of residents of Baku, as well as representatives of the diplomatic corps visited the Alley of Martyrs to commemorate the heroic sons and daughters of Azerbaijan, and laid scarlet carnations at their tombs.